METODE DAKWAH JAMAAH TABLIGH Di MASJID RAYA AT-TAQWA MATARAM - gefa suhirman; Alfiya Magfirah; Nurul Fadilah (UIN Mataram, 2023)
This article explores the preaching movement of the Tablighi Jamaat at the At-Taqwa Mosque, Mataram. The focus of the discussion will be directed to issues regarding the da'wah strategy used to invite people to return to God's teachings. In general, da'wah or preaching is rooted in the word da'a, which means to call and invite. In terms, da'wah means an invitation addressed to humans by Allah and His Messenger, to believe in the true religion, namely Islam. In studying the movement of the Jamaah Tabligh, this article uses the theory of da'wah methodology to see the da'wah used. There are several questions that will be answered in this article, namely, what is the preaching movement of the Tablighi Jamaat?, what strategies are used and how do they implement them in society? The data in this article is the result of field research using a qualitative approach. Meanwhile, the data in this article comes from observations, interviews, and documentation. The results of this study indicate that there are three strategies used by tablighi congregations in preaching in the community, namely deliberation, socializing and mingling with the community, and speaking softly when interacting with the community. Based on these findings, the author argues that the presence of tablighi congregations in the city of Mataram cannot be denied and will continue to grow. Because of that, the da'wah model they developed was very simple and easily accepted by the people, especially in the city of Mataram